PENERAPAN METODE BERMAIN JARI TANGAN DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF PADA ANAK KELAS A DI RAUDHATUL ATHFAL MA’ARIF 01 METRO - Dea, Leli Fertiliana; Setiawan, Agus (Universitas Islam Malang, 2019)
This study aims to determine whether the application of the method of finger play can develop cognitive abilities in class A children in Raudhatul Athfal Ma’arif 01 Metro. This study used a qualitative approach, with the type of Classroom Action Research (CAR). This study uses a design according to the Kemmis model and Taggart MC which consists of four stages, namely: 1. Planning, 2. Action, 3. Observation, and 4. Reflection